Synthesis and Antioxidative Activity of Piperine Derivatives Containing Phenolic Hydroxyl - Bei Qin; Kuan Yang; Ruijun Cao (Journal of Chemistry)
Piperine was used in this study in its raw form, and different steps, such as amide hydrolysis and amidation, were used to synthesize piperine derivatives containing a phenolic hydroxyl group. DPPH and ABTS free radical scavenging assays were used to assess piperine derivative antioxidant activities. We constructed an AAPH oxidative stress erythrocyte model to study the effect of piperine derivatives on the hemolysis rate of oxidatively damaged erythrocytes as well as the hemoglobin oxidation rate. This AAPH model was also used to determine piperine derivative effects on antioxidant enzyme activity and malondialdehyde (MDA) content. Results showed that spectroscopic methods could synthesize and identify piperine derivatives containing phenolic hydroxyl groups (H-1∼H-3). Moreover, DPPH and ABTS assay results showed that piperine derivative free radical clearance rates were higher compared with the parent compound. Additionally, piperine derivatives (H-1∼H-3) were found to provide protection to AAPH oxidatively damaged erythrocytes in their ability to inhibit AAPH-induced erythrocyte lysis, while hemoglobin oxidation was higher compared with the parent compound. Piperine derivatives may protect intracellular glutathione peroxidase (GSH-Px) antioxidant enzyme system activities, safeguarding against oxidative damage. This study synthesized novel piperine derivatives for use as potential antioxidant agent candidates.